Desenvolvimento de treinadores brasileiros experts de judô e taekwondo - Darlan Perondi (2018)
Several factors can influence the development of the sport; among them, the training process deserves to be highlighted because it is directly linked to the improvement of the performance of athletes in competitions. In this context, coaches are primarily responsible for planning and executing the training. Expert coaches can be defined as coaches who have extensive training knowledge and apply this knowledge to improve athletes' performance. In addition, expert coaches have other characteristics such as ten years of continuous experience; accumulated positive results in competitions, experience as a national team coach, and experience in training high-level athletes. The study aimed to verify the development of expert coaches of Judo and Taekwondo. Twenty-one Brazilian Judo and Taekwondo coaches were divided into of five categories: Men’s Expert Judo Coaches (n = 7), Women´s Expert Judo Coaches (n = 3), Men´s Expert Taekwondo Coaches (n = 9), Women Expert Coach of Taekwondo (n = 1) and Men´s Expert Coach of Taekwondo in 1990s (n = 1). After a review of the literature on the development of expert coaches, a semi-structured interview was elaborated addressing the main factors related to the development of coaches. Data analysis was performed through content analysis using the deductive method. A matrix of deductive analysis with pre-defined categories was elaborated. Besides, new categories emerged by the inductive method of the content analysis. The results presented several categories related to the development of expert coaches, among them, are personal characteristics, formal learning, informal learning and influences of family and friends. In addition, differences can be observed between the development of men's coaches expert and women's coaches expert in Judo and Taekwondo, as well as differences between the development of Taekwondo expert coach of the 1990s and the development of current Taekwondo expert coaches.